2005
DOI: 10.1016/j.jcrs.2005.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness measurement with the Pentacam Scheimpflug system, optical low-coherence reflectometry pachymeter, and ultrasound pachymetry

Abstract: Objective, noncontact measurement of central corneal thickness with the Pentacam Scheimpflug system and OLCR pachymeter was convenient and yielded excellent intraoperator repeatability and interoperator reproducibility. Central corneal thickness values obtained with the Pentacam were similar to those obtained with both the OLCR pachymeter and an US pachymeter. Further research is needed to corroborate whether central corneal thickness measurements by the Pentacam and OLCR devices can be used interchangeably an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
198
5
22

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(238 citation statements)
references
References 24 publications
13
198
5
22
Order By: Relevance
“…It has been used in the assessment of cataract 6 and for measuring corneal curvature and thickness. 7 From the images acquired, information regarding the anterior and posterior corneal elevation, pachymetry, asphericity, anterior chamber depth, angle and lens density can be measured quickly and noninvasively. Using this device, we can obtain important data, which are required for early diagnosis, followup and surgical planning in keratoconus patients.…”
Section: /Jp-journals-10025-1017mentioning
confidence: 99%
“…It has been used in the assessment of cataract 6 and for measuring corneal curvature and thickness. 7 From the images acquired, information regarding the anterior and posterior corneal elevation, pachymetry, asphericity, anterior chamber depth, angle and lens density can be measured quickly and noninvasively. Using this device, we can obtain important data, which are required for early diagnosis, followup and surgical planning in keratoconus patients.…”
Section: /Jp-journals-10025-1017mentioning
confidence: 99%
“…Using the Pentacam system, Amano et al (1) found an average corneal thickness of 538±31.3 µm in 54 Japanese subjects, which were in good correlation with ultrasonic and scanning-slit pachymetry. In agreement with these findings, Buehl et al (13) and Barkana et al (14) concluded that the Pentacam is a reproducible, reliable and easy to use non-contact method of measuring CCT. Lackner et al (15) compared the repeatability and reproducibility of CCT with the Pentacam, Orbscan and ultrasound concluding that Pentacam's reproducibility was the highest of all.…”
Section: Discussionmentioning
confidence: 55%
“…[13][14][15][16] This method has been reported to have a high degree of intraoperator and interoperator reproducibility. [4] Placement of the probe on the corneal center can lead to operator-dependent errors due to offcenter placement (thicker measurements) , [17,18] indentation (thinner readings) [19] are the drawbacks of pachymeter.…”
Section: Discussionmentioning
confidence: 99%